An Empirical Analysis and Evaluation of Internet Robustness - Stampanoni, Michele (School of Economics, 2023)
The study of network robustness is a critical tool in the understanding of complex interconnected systems such as the Internet, which due to digitalization, gives rise to an increasing prevalence of cyberattacks. Robustness is when a network maintains its basic functionality even under failure of some of its components, in this instance being nodes or edges. Despite the importance of the Internet in the global economic system, it is rare to find empirical analyses of the global pattern of Internet traffic data established via backbone connections, which can be defined as an interconnected network of nodes and edges between which bandwidth flows. Hence in this thesis, I use metrics based on graph properties of network models to evaluate the robustness of the backbone network, which is further supported by international cybersecurity ratings. These cybersecurity ratings are adapted from the Global Cybersecurity Index which measures countries' commitments to cybersecurity and ranks countries based on their cybersecurity strategies. Ultimately this empirical analysis follows a three-step process of firstly mapping the Internet as a network of networks, followed by analysing the various networks and country profiles, and finally assessing each regional network's robustness. By using TeleGeography and ITU data, the results show that the regions with countries which have higher cybersecurity ratings in turn have more robust networks, when compared to regions with countries which have lower cybersecurity ratings.